Hemorheological Changes in Elderly Subjects-Effect of Pentosan Polysulfate and Possible Role of Leucocyte Arachidonic Acid Metabolism - Freyburger, G; Larrue, F; Manciet, G; Lorient-Roudaut, M F; Larrue, J; Boisseau, M R (Thrombosis and Haemostasis, 1987)
The effects of pentosan polysulfate (PPS) on various hemorheological parameters were studied in a group of very elderly subjects in good general health. Alterations in blood viscosity and filterability were detected in these patients, without any concomitant changes in factors which are known to affect these parameters: notably hematocrit, fibrinogen and plasma lipid levels. The hemorheological abnormalities were considerably improved by twice daily treatment with 50 mg of PPS (i.m.).Apart from its anticoagulant activity, PPS has been shown to have an anti-inflammatory action. We were interested to investigate its effects on metabolism of exogenous arachidonic acid (AA) by both platelets and leucocytes. It is becoming increasingly recognized that metabolites of AA via the 5 LO pathway appear to play a role in inflammatory processes. In this study, PPS was found to inhibit leucocyte 5 LO activity. Reduction in the levels of these metabolites may therefore have an effect on whole blood rheology.
Keywords: Elderly; Pentosan polysulfate; Hemorheology; Arachidonic acid; Leucotrienes; Leucocyte